CECI N’EST PAS UNE COLLECTION... OU É?: CONCEITO E PROTEÇÃO DAS COLEÇÕES DE ARTE À LUZ DO DIREITO COMPARADO - MOREIRA, Gustavo Tanouss de Miranda (2020)
Art collections are ubiquitous in the contemporary Western world and are increasingly present in Eastern countries. Nowadays, artworks represent not only luxury articles for aesthetic pleasure, but investment goods, unique creations of the human genius, witnesses of the past, objects of study, sources of social prestige, decorative items and, above all, common cultural heritage to be safeguarded, some portions of life that, once lost, cannot be replaced: quite diverse motivations that converge nonetheless in the spaces of public and private collections. Private individuals; companies, corporations and powerful financial institutions; robust public museums and humbler cultural and museological structures: here are the art collectors par excellence. Notwithstanding the pressing relevance and the old need, national and international lawmakers and the legal doctrines only in recent times seem to have awakened to the specific protection of art collections. To protect them legally requires the law to conceptualise them, considering the essential elements that characterise them and allowing that the most effective protection possible be granted to them. Moreover, the adequate legal protection of art collections imposes not only the protection of each element that composes them, but also of art collections taken as a whole, applying to them a specific legal regime, that sees them as entities in themselves. This work brings to light the importance of the legal concept of art collection and, through a comparative approach, examines such a concept in various European legal systems, as well as in the Brazilian, European Union and international laws. Furthermore, analyses in greater depth how French law protects art collections, doing the same in relation to Brazilian law and, in the end, outlines a comparison between both systems concerning the subject matter. Against the background that French collections law constitutes one of the most advanced in the world, even though presenting imperfections and limitations which demand polishing, and that the Brazilian legal system, however offering a relatively good protection to works of art, appears to be still incipient when it comes to the effective protection of set collections, the comparison drawn between the central points of the law of collections in France and in Brazil has the power to contribute some valuable lessons, enabling the Brazilian legal system to benefit from the highly developed French experience. We expect, therefore, that the present work will propel Brazil into following the good examples à la française, inducing the country to rise into a global cultural power, including in the realm of art law